Chemotherapy-induced adverse drug reaction of antineoplastic drugs among oncology patients in a tertiary care teaching hospital - Harshakumar, Sabarinath; Kurian, Sherin V.; James, Josmi; George, Fiyona K.; Jose, Sonatta Monica (International Journal of Research in Medical Sciences, 2024)
Background: The main objectives of the study were to assess the pattern of adverse drug reactions (ADRs) associated with the use of antineoplastic drugs along with their causality and severity. The study also aims to analyse the different stages of cancer, cycles of chemotherapy and the quality of life of the patients. Methods: This prospective, cross-sectional and descriptive study was conducted among 100 patients of either sex for 6 months from April 2023 to October 2023. This study included patients above the age of 18 years who were clinically diagnosed with cancer and prescribed at least one antineoplastic drug. Results: Most of the cancer patients belonged to stage 2 and were undergoing the third cycle of chemotherapy. Most common ADRs were alopecia, anemia and anorexia. The study revealed that 79% of ADRs were possible and nearly 21% were probable in nature. After the severity assessment, it was found that all of the ADRs were mild (level 1). It was also identified that quality of life (QoL) decreases with advancing stages of cancer. Conclusions: Cancer, along with therapeutic agents, can impair a patient's quality of life, prompting the development of effective management strategies. Assessing the severity and causation of ADRs can help determine the right supportive care agent to improve patients' general well-being.